2020
DOI: 10.1111/ijcp.13594
|View full text |Cite
|
Sign up to set email alerts
|

Extranodal site of diffuse large B‐cell lymphoma and the risk of R‐CHOP chemotherapy resistance and early relapse

Abstract: Background About 20%‐30% of diffuse large B‐cell lymphoma (DLBCL) patients experience early disease progression despite R‐CHOP chemotherapy treatment. Revised international prognostic index (R‐IPI) score could risk stratify DLBCL patients but does not identify exactly which patient will be resistant to R‐CHOP therapy or experience early relapse. Aims of the Study To analyse pre‐treatment clinical features of DLBCL patients that are predictive of R‐CHOP therapy resistance and early disease relapse after R‐CHOP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Taking these findings into consideration, among patients whose disease extent was limited to the same side of the diaphragm but were not classified as stage 1 DLBCL, the following subgroups were classified as “modified stage II” disease: 1) patients with nodal lesions only, 2) patients with single extranodal lesion that was contiguous to the nodal lesion, and 3) patients with single extranodal lesion that was non-contiguous to the nodal lesion. In contrast, patients with ≥2 extranodal involvement showed significantly inferior PFS and OS compared with the modified stage II DLBCL patients in this study, which was consistent with previous studies ( 2 , 9 ). These results suggest that the amount of extranodal involvement, rather than the presence of extranodal involvement itself or the anatomic contiguity of the lesion, is a more important prognostic factor for patients with DLBCL on the same side of the diaphragm.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Taking these findings into consideration, among patients whose disease extent was limited to the same side of the diaphragm but were not classified as stage 1 DLBCL, the following subgroups were classified as “modified stage II” disease: 1) patients with nodal lesions only, 2) patients with single extranodal lesion that was contiguous to the nodal lesion, and 3) patients with single extranodal lesion that was non-contiguous to the nodal lesion. In contrast, patients with ≥2 extranodal involvement showed significantly inferior PFS and OS compared with the modified stage II DLBCL patients in this study, which was consistent with previous studies ( 2 , 9 ). These results suggest that the amount of extranodal involvement, rather than the presence of extranodal involvement itself or the anatomic contiguity of the lesion, is a more important prognostic factor for patients with DLBCL on the same side of the diaphragm.…”
Section: Discussionsupporting
confidence: 92%
“…Previous retrospective studies reported poorer survival outcomes of extranodal disease compared with nodal disease among patients with stage 1 DLBCL or in the overall DLBCL population ( 9 11 ). However, few studies have reported the prognostic implication of extranodal disease among patients with Ann Arbor stage 2 DLBCL or patients with disease involving the same side of the diaphragm.…”
Section: Discussionmentioning
confidence: 95%
“…9 In fact, patients with poor response to R-CHOP have a 1-year overall survival. 10 The expression of programmed death-ligand 1 protein (PD-L1) is upregulated in tumors. 11,12 PD-L1 binding to the PD-1 receptor on immune cells results in tolerance for tumor antigens and the down regulation of T-cells.…”
Section: Introductionmentioning
confidence: 99%
“…The median age for DLBCL is between the sixth and seventh decade of life. Diffuse Large B-cell Lymphomas can arise in an extranodal organ in up to 30% of cases with the most common sites being gastrointestinal tract, skin and soft tissue, bone or genitourinary tract [ 2 ]. DLBCLs are rare in the soft tissue of the upper extremity.…”
Section: Introductionmentioning
confidence: 99%